Gender issue in rural lowland management and development in Southern Sumatra - Winarno, Bondan (Balitbank LHK, 2019)
Presented by Bondan Winarno (Balitbank LHK), as part of the Annual Scientific Conference hosted by the University of Canberra and co-sponsored by the University of Canberra, the Australian Centre for International Agricultural Research (ACIAR) and CGIAR Collaborative Platform for Gender Research, Canberra, Australia, April 2-4, 2019.